PRODUCT LIFE CYCLE MAIN COMMODITIES AND TYPE OF BUSINESS CAPE TOWN CENTER - Gustina Siregar; Desi Novita (AGRIUM: Jurnal Ilmu Pertanian, 2016)
Micro, small and medium enterprises (SMEs) in the economy has an important role and strategis.Pembinaan and pengembanganUMKM is a necessity in order to improve the regional economy. Given the variety and range of SME varies widely both in quantity and coverage is almost at all sectors of the economy so that it appears management problems of SMEs that do not focus on commodities and potensial.Kondisi type of business that can have impact on the promotion and development of SMEs which do not have efektif.Penelitian aims to determine the life cycle of commodities and types of businesses as well as the strategy of development of SMEs featured in Tanjungbalai so that it can support the improvement of the regional economy in KotaTanjungbalai. The data used in the analysis method Product Life Cycle analysis and SWOT analysis. The results showed that fish salting business, financial services, trade of fishery products, aquaculture clams, sea fishing, the fish meal industry business, the business of merchants of agricultural and minimarket business has relatively better prospects when compared to fish farming ditambak and budidaya.Sedangkan development potential varies from very high, high and medium. Alternative development model for the development of SMEs in Tanjungbalai is expected through the formation of clusters by strengthening the agribusiness system from upstream to downstream (Value Chain Agribusiness).Keywords: SMEs, Cycle, Commodities and Commodity Business Type